Adjoint network method applied to the performance sensitivities of microwave amplifiers - Gunes, F.; Guroglu, N. (WILEY, 2006)
This work focuses on the performance sensitivities of microwave amplifiers using the adjoint network and adjoint variable method, via wave approaches, which includes sensitivities of the transducer power gain, noise figure, and magnitudes and phases of the input and output reflection coefficients. The method can be extended to sensitivities of the other performance measure functions. The adjoint-variable methods for design-sensitivity analysis offer computational speed and accuracy. They can be used for efficiency-based gradient optimization, in tolerance and yield analyses. In this work, an arbitrarily configured microwave amplifier is considered: firstly, each element in the network is modeled by the scattering matrix formulation, then the topology of the network is taken into account using the connection scattering-matrix formulation. The wave approach is utilized in the evaluation of all the performance-measurement functions, then sensitivity invariants are formulated using Tellegen's theorem. Performance sensitivities of the T- and Pi-types of distributed-parameter amplifiers are considered as a worked example. The numerical results of T- and Pi-type amplifiers for the design targets of noise figure F-req = 0.46 dB double left right arrow 1,12 and V-ireq = 1, G(treq) = 12 dB double left right arrow 15.86 in the frequency range 2-11 GHz are given in comparison to each other. Furthermore, analytical methods of the gain factorisation and chain sensitivity parameter are applied to the gain and noise sensitivities as well. In addition, numerical perturbation is applied to calculation of all the sensitivities. (c) 2006 Wiley Periodicals, Inc.
Keywords: adjoint network; adjoint variables; wave sensitivity; connection scattering matrix; transducer gain; noise figure; input reflection coefficient; output reflection coefficient; matching circuit; chain parameters; Computer Science; Engineering